Synthesis and Evaluation of Biological Activities of Aziridine Derivatives of Urea and Thiourea - Aleksandra Kowalczyk; Adam M. Pieczonka; Michał Rachwalski; Stanisław Leśniak; Paweł Stączek (Molecules, 2017)
In the present paper, we report the synthesis and evaluation of in vitro antimicrobial activities of aziridine-thiourea derivatives. A series of aziridines in reaction with isocyanates and isothiocyanates to obtain urea and thiourea derivatives were used. The structures of all new products were confirmed based on spectroscopic data (1H-NMR, 13C-NMR, HR-MS). These compounds were screened for their in vitro antimicrobial activity against a panel of Gram-positive and Gram-negative strains of bacteria. Six of the tested compounds appeared to be promising agents against reference strains of Escherichia coli, Staphylococcus aureus and Staphylococcus epidermidis. Subsequently, compounds exhibiting promising antibacterial activity were tested against twelve clinical isolates of S. aureus from three different sources of infection. The most bactericidal compounds (MIC = 16–32 µg/mL) showed better antibacterial activity against MRSA than ampicillin and streptomycin. The in vitro cytotoxicity analysis on L929 murine fibroblast and HeLa human tumor cell line using the MTT assay allowed us to select the least toxic compounds for future investigation.